Regulation of the Intestinal Barrier Function by Host Defense Peptides - Robinson, Kelsy; Deng, Zhuo; Hou, Yongqing; Zhang, Guolong (Frontiers in Veterinary Science, 2015)
Intestinal barrier function is achieved primarily through regulating the synthesis of mucins and tight junction proteins, which are critical for maintaining optimal gut health and animal performance. An aberrant expression of tight junction proteins results in increased paracellular permeability, leading to intestinal and systemic disorders. As an essential component of innate immunity, host defense peptides (HDPs) play a critical role in mucosal defense. Besides broad-spectrum antimicrobial activities, HDPs promotes inflammation resolution, endotoxin neutralization, wound healing, and the development of adaptive immune response. Accumulating evidence has also indicated an emerging role of HDPs in barrier function and intestinal homeostasis. HDP deficiency in the intestinal tract is associated with barrier dysfunction and dysbiosis. Several HDPs were recently shown to enhance mucosal barrier function by directly inducing the expression of multiple mucins and tight junction proteins. Consistently, dietary supplementation of HDPs often leads to an improvement in intestinal morphology, production performance, and feed efficiency in livestock animals. This review summarizes current advances on the regulation of epithelial integrity and homeostasis by HDPs. Major signaling pathways mediating HDP-induced mucin and tight junction protein synthesis are also discussed. As an alternative strategy to antibiotics, supplementation of exogenous HDPs or modulation of endogenous HDP synthesis may have potential to improve intestinal barrier function and animal health and productivity.